Severe Little Ice Age drought in the midcontinental United States during the Mississippian abandonment of Cahokia - David P. Pompeani (Nature Portfolio, 2021)
Abstract Drought has long been suspected as playing an important role in the abandonment of pre-Columbian Native American settlements across the midcontinental United States between 1350 and 1450 CE. However, high-resolution paleoclimatic reconstructions reflecting local effective moisture (the ratio of precipitation to evaporation) that are located in proximity to Mississippi period (1050–1450 CE) population centers are lacking. Here, we present a 1600-year-long decadally resolved oxygen isotope (δ18O) record from Horseshoe Lake (Collinsville, IL), an evaporatively influenced oxbow lake that is centrally located within the largest and mostly densely populated series of Mississippian settlements known as Greater Cahokia. A shift to higher δ18O in the Horseshoe Lake sediment record from 1200 to 1400 CE indicates that strongly evaporative conditions (i.e., low effective moisture) were persistent during the leadup to Cahokia’s abandonment. These results support the hypothesis that climate, and drought specifically, strongly impacted agriculturally based pre-Columbian Native American cultures in the midcontinental US and highlights the susceptibility of this region, presently a global food production center, to hydroclimate extremes.